Drosophila SnoN modulates growth and patterning by antagonizing TGF-beta signalling. - Ramel, M; Emery, C; Emery, C; Foulger, R; Goberdhan, D; van den Heuvel, M; Wilson, C (2007)
Signalling by TGF-beta ligands through the Smad family of transcription factors is critical for developmental patterning and growth. Disruption of this pathway has been observed in various cancers. In vertebrates, members of the Ski/Sno protein family can act as negative regulators of TGF-beta signalling, interfering with the Smad machinery to inhibit the transcriptional output of this pathway. In some contexts ski/sno genes function as tumour suppressors, but they were originally identified as oncogenes, whose expression is up-regulated in many tumours. These growth regulatory effects and the normal physiological functions of Ski/Sno proteins have been proposed to result from changes in TGF-beta signalling. However, this model is controversial and may be over-simplified, because recent findings indicate that Ski/Sno proteins can affect other signalling pathways. To address this issue in an in vivo context, we have analyzed the function of the Drosophila Ski/Sno orthologue, SnoN. We found that SnoN inhibits growth when overexpressed, indicating a tumour suppressor role in flies. It can act in multiple tissues to selectively and cell autonomously antagonise signalling by TGF-beta ligands from both the BMP and Activin sub-families. By contrast, analysis of a snoN mutant indicates that the gene does not play a global role in TGF-beta-mediated functions, but specifically inhibits TGF-beta-induced wing vein formation. We propose that SnoN normally functions redundantly with other TGF-beta pathway antagonists to finely adjust signalling levels, but that it can behave as an extremely potent inhibitor of TGF-beta signalling when highly expressed, highlighting the significance of its deregulation in cancer cells.